(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
Combined power plants are more efficient in converting thermal energy into electrical energy due to the advancement of technology in the world. A simple gas turbine unit is integrated with a steam unit to form a combined cycle unit, utilizing a Heat Recovery Steam Generator (HRSG) to recover waste heat from the gas turbine exhaust and generate additional power without additional fuel consumption The present study aims to model a simple gas turbine power generation plant along with a single-pressure Heat Recovery Steam Generator (HRSG) and conduct a thermal analysis under varying operating conditions, specifically ambient temperature and atmospheric pressure (1 bar). The study focuses on the gas power generation plant in the Al-Qayyarah district, south of Mosul, which is designed with a generation capacity of up to (125 MW). The objective is to determine the operational parameters of the single-pressure HRSG in relation to its engineering design, should the gas turbine plant be converted into a combined cycle unit. This analysis considers energy balance, the mass flow rate of exhaust gases from the gas turbine, and the steam production rate from the HRSG. The results indicate that an increase in ambient temperature at constant atmospheric pressure negatively impacts the performance of the simple gas turbine unit. Specifically, thermal efficiency, power generation capacity, and exhaust gas mass flow rate decrease, while exhaust gas temperature and fuel consumption rate increase. The results also showed that increasing ambient temperature negatively affects the performance of the combined cycle power generation unit by reducing the gas turbine power output due to lower air density. However, it leads to an increase in exhaust gas temperature, which may slightly improve HRSG effectiveness and steam production but generally results in a decline in overall cycle efficiency and generating capacity. Analysis of the results indicates that a significant amount of thermal energy, approximately 60%, is lost with the exhaust gases from the combustion process in the gas turbine unit. However, this waste heat can be recovered and utilized to generate additional power and improve overall thermal efficiency by integrating the gas turbine with a steam unit through a Heat Recovery Steam Generator (HRSG), forming a combined cycle power generation system.